2016
DOI: 10.4314/sajg.v5i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the potential of remote sensing to discriminate invasive <i>Seriphium plumosum</i> from grass

Abstract: The usefulness of remote sensing to discriminate Seriphium plumosum from grass using a field spectrometer data was investigated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Their research showed some parts of the study area had constantly been burnt with high fire severity over 20 years. These parts of the study area may be experiencing changes in species composition, leaving only the fire-tolerant species or invasive species like S. plumosum, which is a known species that promote the spread of wildfires (52)(53)(54). In fires recently disturbed areas in the park, S. plumosum can sprout and lie dormant when encountering higher temperatures and lowmoisture conditions for the remainder of winter while awaiting the emergence of spring (55).…”
Section: Figure 11: Species Contributions To Change In Phragmites Australismentioning
confidence: 99%
“…Their research showed some parts of the study area had constantly been burnt with high fire severity over 20 years. These parts of the study area may be experiencing changes in species composition, leaving only the fire-tolerant species or invasive species like S. plumosum, which is a known species that promote the spread of wildfires (52)(53)(54). In fires recently disturbed areas in the park, S. plumosum can sprout and lie dormant when encountering higher temperatures and lowmoisture conditions for the remainder of winter while awaiting the emergence of spring (55).…”
Section: Figure 11: Species Contributions To Change In Phragmites Australismentioning
confidence: 99%
“…In other cases, on-ground reference data acquisition is necessary, especially for herbaceous plants characterized by high phenological variability and growing in heterogenous, species-rich ecosystems. This latter kind of reference data acquisition is often labor-intensive, expensive, and sometimes not feasible due to land inaccessibility [12,13]. The percentage cover of herbaceous plants in natural ecosystems changes significantly over intra- and inter-annual time periods.…”
Section: Introductionmentioning
confidence: 99%